POLA KOMUNIKASI DALAM SANGKEPAN DESA ADAT PENGLIPURAN KECAMATAN BANGLI KABUPATEN BANGLI - I Dewa Ayu Komang Raka Dharmayanti; Relin D.E; I Nyoman Ananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Traditional village leaders, in this case kelian desa, are the main authorities in managing traditional villages in Penglipuran traditional village, Kubu sub-district, Bangli sub-district, Bangli district, so they need to have innovative capabilities and initiative in leading their traditional villages. In this regard, effective communication efforts are also implemented in the traditional Penglipuran village, especially in the customary decision-making process which is carried out through deliberations for consensus in a traditional village meeting or better known as the traditional village pesantren, with the hope that what is planned, discussed and decided in sangkepan can make society harmonious, peaceful gemah ripah loh jinawi kerta raharje.Based on this background, the researcher is interested in researching